Britain's military role in defending Belgium in the years of World War I 1914-1918 AD - Khalaf, Hind Zidan (Journal of Tikrit University for Humanities, 2023)
After the British government sent its ultimatum to Germany and did not find respect for Belgium's neutrality acceptable to the German government, it expressed its willingness to join France and take joint military action against Germany; To defend Belgium's neutrality and maintain its independence, it declared war on Germany on August 4, 1914; To confront the German forces advancing inside Belgian territory in conjunction with the French forces. Therefore, this research will deal with Britain's declaration of war on Germany, and Britain's attempt to confront Germany within the Belgian lands, which became a theater of battles between the great powers during the First World War. It will also discuss the analysis of British motives to protect Belgium, then evaluate the German claims to penetrate Belgium's neutrality and independence, and then the British role. and the French Liberation of Belgium, which was accomplished by Germany's surrender on November 11, 1918.